Aluminium chloride for hyperhidrosis. Issue 26 (18th December 1981) - Unknown
Abstract : Hyperhidrosis is often embarrassing, and when it is severe most antiperspirants sold over the counter are ineffective. The first line of therapy is to correct any underlying medical disorder such as acromegaly or hyperthyroidism. However, in the majority of patients symptomatic treatment alone is appropriate. Specialists have long prescribed topical aluminium chloride hexahydrate for axillary hyperhidrosis and two preparations are available for general use, Anhydrol Forte (Dermal) and Odaban (Bracey).